Aplikasi Kompos Jerami dan Pupuk Kotoran Walet Terhadap Pertumbuhan dan Produksi Kedelai (Glycine max L. Merill) - Fardyansyah Hasan; Muh Jabal Nur (JURNAL GALUNG TROPIKA, 2021)
This study aims to determine the effect of applying straw compost and swallow manure and their interaction on the growth and production of soybean plants. The study was conducted in the garden of Tinelo Village, Tilango District, Gorontalo Regency, from February to July 2021. The study was arranged using a randomized block design with two factors and three replications. The first factor is the dose of straw compost, consisting of three levels, namely without the application of straw compost, 10 tons ha-1 , and 15 tons ha-1. The second factor was the dose of wallet manure, consisting of three levels, namely without fertilizer application, swallow manure 5 tons.ha-1 and 10 tons.ha-1. The results showed that the application of swallow manure fertilizer at a dose of 10 tons ha-1 was the best treatment by producing the highest number of pods and 100 seeds and increasing soybean seed weight up to 13.56 %.